PENGARUH KOMPETENSI PEGAWAI, PENEMPATAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI - Mulyani, Sitti Rizki (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UPI YPTK PADANG, 2019)
ABSTRACT This research was conducted at the Secretariat of the Department of Religion. Strikes with the aim to find out how much influence, Employee Competence, Job Placement, and Career Development, on Employee Performance at the Secretariat of the Department of Religion. 75 respondents. Questionnaires distributed as much as 75 and can be processed, The analytical method used is regression analysis and correlation analysis. The results obtained based on Partial Test (t test) are obtained: (a) there is a positive and significant influence between Competence on Employee Performance, evidenced by the value t count is greater than t table. (b) There is a positive and significant influence between Job Placement on Employee Performance, evidenced by the value of t calculated is greater than t table. (c) There is a positive and significant influence between Career Development on Employee Performance, as evidenced by the value of t calculated greater than t table . Then based on hypothesis testing together (Test F) it can be seen that employee competence, work placement, and career development have a positive and significant effect on employee performance. And by testing the coefficient of determination (R2)showed that the percentage of the competence of Employees, Job Placement and Career Development to variable affects employee performance in other variables such as mutations, organizational climate, motivation, and others.   Keywords: Competence, Job Placement, Career Development